Role of Hepatobiliary Scintigraphy and Ultrasonography in the Diagnosis of Biliary Atresia in Infant with Neonatal Jaundice – Experiences in NINMAS (Bangladesh Journal of Nuclear Medicine, 2017)
Objective: The purpose of this study was to determine whether gall bladder visualization can help to exclude the biliary atresia in hepatobiliary scintigraphic studies of infants with persistent jaundice.Methods: This is a retrospective study carried out at the National Institute of Nuclear Medicine and Allied Sciences (NINMAS). Study subjects include infants with neo-natal jaundice who underwent Hepatobiliary scintigraphies for suspected biliary atresia and study period was 2 years. Food was withheld for 4 hours before the examination. Anterior images of liver and gall bladder were taken after i/v administration of 2 -3 mci 99m Tc labeled Brida (HIDA) at 5 min interval for 2 hours then at 4 hours and 24 hours. Non-visualization of bowel activity in HIDA scan in 24hours delayed images was considered as cases of diagnosis of biliary atresia.Results: Thirty-six patients were included in this retrospective study. Patent biliary channels was seen by scintigraphies in 17(47%) patients and biliary atresia was seen in 19(52%) patients. By abdominal US non- visualization of gall bladder were found in 25(69%) cases and gall bladder visualized in 11(30%) cases. Eight (22%) of 36 patients had biopsy confirmed biliary atresia; all of these had positive scintigraphies and (60%) had positive sonographic findings. Among the 5 false-positive scintigraphies caused by hepatic dysfunction and 2 had normal sonography. Thirty-six patients had periscintigraphic sonography. There were 25/36 (61%) abnormal studies, which included cases with small gallbladder (n = 8) and non-visualized gallbladder (n = 17), but not periportal fibrosis.Conclusion: Gall bladder was usually visible on Hepatobiliary scintigraphy of fasting patients with biliary patency.  Both hepatobiliary scintigraphy and sonography are currently the standard imaging investigations for suspected biliary atresia. The complementary role, in which scintigraphy and sonography are important, and recommend follow-up imaging reassessment before making definitive surgical decisions. This will serve to decrease the frequency of false-positive imaging diagnoses of biliary atresia, and hence, avoid unnecessary surgeries.Bangladesh J. Nuclear Med. 18(1): 51-53, January 2015